Postinjury performance for differing humeral stress fracture locations in the racing thoroughbred. Issue 7 (17th July 2020) - Henderson, Brianne; Bramlage, L. R.; Koenig, Judith; Monteith, Gabrielle
Abstract: Objective: To assess the influence of humeral stress fracture location on the time to return to racing and postinjury performance of thoroughbred racehorses. Study design: Retrospective study (1992‐2015). Sample population: Thoroughbred racehorses (n = 131) that presented for lameness with the sole diagnosis of humeral stress fractures in the lame limb, as determined by scintigraphy or radiology. Methods: Sex, fracture site, age, starts, earnings, and average earnings per race were examined for differences in pre–stress and post–stress fracture diagnosis for the entire population as well as individual stress fracture locations (general linear model, χ 2 tests). Pre–stress and post–stress fracture performance for the three stress fracture locations were assessed: (1) earnings pre–stress and post–stress fracture (Kruskal‐Wallis one‐way analysis of variance), (2) average earnings per start prefracture, and (3) average earnings per start postfracture (Wilcoxon signed‐rank tests). Results: Stress fracture locations were caudodistal (n = 36), craniodistal (n = 43), and caudoproximal (n = 52). One hundred ten of 131 horses raced postfracture, and 54 of 131 horses raced prefracture. Age at injury was 43.61 months caudodistal, 33.48 months caudoproximal, and 36.65 months craniodistal. Horses returned to race at a median of 244 days (range, 218‐272). Postfracture earnings per start were greater for caudodistal vs caudoproximal ( P = .04). Conclusion: There were no differences in prefracture earnings or fracture site and sex or limb affected. Return‐to‐race time varied by location but not significantly. Differences in earnings preinjury and postinjury were not significant. Horses with a stress fracture at the caudodistal location earned significantly more compared with horses with a stress fracture at the caudoproximal location after they returned to race. Clinical significance: Thoroughbred racehorses have a good prognosis for return to racing regardless of fracture location.